MANEUVERING PERFORMANCE OF A 30 GT FISHING VESSEL WITH ASYMMERICAL PROPELLER CONFIGURATION - Andi Haris Muhammad; . Syarifuddin; Daeng Paroka; Sabaruddin Rahman; . Wisyono; Andi Angga Pratama (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Fishing vessels are designed with a specific mission. That mission is to locate, catch, and preserve fish while out at sea, meanwhile the vessel needed to have good maneuverability. This research describes a study on asymmetrical propeller configuration of a fishing vessel to improve its maneuvering quality. MATLAB-simulink program was used to simulate, the turning circle and the zigzag maneuvers. The simulation program was developed based on the mathematical model for a fishing vessel maneuvering. The mathematical model involved the setting-up a 3 DOF (Degres of Freedom) mathematical model in a modular of MMG (Mathematical Modeling Group) of the hull, propeller and rudder component. The result indicated that twin propeller with asymmetrical had an advantages of turning circle ability of 8% to 14 %, meanwhile the zigzag maneuver 20°/20° had 9 to 20 % 1st overshoot different between left and right heading. Keywords: Configuration, propeller, assymetrical, fisheries, simulation